Factors that contribute to high Non-Performing Loan (NPL): A case study on Agrobank, Dungun branch, Terengganu Darul Iman / Mohammad Firdaus Ismail - Ismail, Mohammad Firdaus (2010)
The aim of this paper is to investigate the factors that contribute to high non-performing loan in the banking system but more focus on the study at Agro Bank, Dungun branch. From that, we want to investigate the most determinant factor that contributes to the high NPL. From that, the researcher investigates the determinant of high NPL in the case of Agro Bank, Dungun branch, which is a commercial bank that focuses its lending in agricultural sector. The data used in this study is gathered through a survey on 100 respondents that are carried out in Agro Bank, Dungun branch. In this study, the determinants are divided into three; customers’ financial condition, customers’ attitude and banking management. The result of this study shows that the probability for high NPL is mostly influenced by the customers’ financial condition. For the banking management and customers' attitude variables, there is less influence to the high NPL at Agro Bank, Dungun branch.